PENGARUH OLAHRAGA JALAN SANTAI TERHADAP KUALITAS TIDUR LANSIA DI PANTI WERDHA BANDUNG - Setyarini, Elizabeth Ari; Sihombing, Ferdinan; Sandriani, Veronika Ayu (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
In the elderly complaints arising from difficulty sleeping at night, where sleep episodes tend to be short, and almost do not have a deep sleep. If this continues, there is a risk of disturbance in the quality of sleep in the elderly The phenomenon that occurs in the elderly is found 4 out of 5 elderly complained of not being able to sleep well at night, during the day often evaporates, no concentration and the lower conjunctiva looks black. The purpose of this study was to determine the effect of a relaxing walk on the quality of sleep in the elderly. This research uses quantitative methods, quasi-experimental design with a pre and post without control approach. The sample of this study used a purposive sampling technique, 10 respondents. Instrument for assessing sleep quality: using PSQI. Univariate research results obtained pre-test data that 100% of elderly have poor sleep quality and post-test results obtained 90% of poor elderly sleep quality and 10% of good sleep quality. Paired T-Test samples obtained p value 0,000 <? (0.05 means that there is an influence of walking to the quality of sleep in the elderly. Suggestion in this research is to schedule a 3-week walk in the orphanage environment to improve the quality of sleep in the elderly.